Reflections on the Don-Juan Text in Russian Literature - Szymańska, Aleksandra (Acta Universitatis Lodziensis. Folia Litteraria Rossica, 2015)
The author of the paper considers the possibility of creating in the Russian theory of literature, by way of analogy to the ‘Petersburg text,’, the ‘Don-Juan text’ of Russian literature. To this purpose, a complex of permanent futures shared by literary works that refer to Don Juan are described. The existence of a ‘Don-Juan text’ is evidenced by a group of literary works that employ the archetype of the famous seducer. Other indicators are: the presence of mythological structure, connection with the spheres of the sacred and the profane, constants in Don Juan’s behaviour, specific vocabulary, classifying the most recurrent words and phrases according to their semantics and function in the text.